Improving targeting feedback for users with low visibility using visual redundant feedback - Sim, Dennis Chee Chow (Faculty of Computer Science and Information Technology, 2005)
A key problem with mobile computing devices is the limited screen space, which cannot be physically made larger to allow the devices to be able to fit in the hand or pocket for mobility. A small screen can become cluttered with information, resulting in devices that are hard to use,with objects that is difficult to identify and select. A solution to overcome this is to increase the object size when the pointer moves near it. The paper describes an experiment to study the optimal growth rate to apply to a target object to enhance the targeting of graphically augmented buttons on mobile computing devices.